Assessment of whole body MRI and sestamibi technetium-99m bone marrow scan in prediction of multiple myeloma disease progression and outcome: a prospective comparative study. Issue 1 (10th January 2013) - Khalafallah, Alhossain A; Snarski, Andrew; Heng, Robert; Hughes, Ryan; Renu, Shamsunnaher; Arm, Jameen; Dutchke, Richard; Robertson, Iain K; To, Luen B
Abstract : Objectives: This study aims primarily to determine whether whole body MRI (WB-MRI) and Sestamibi Technetium-99m-bone marrow (MIBI) scans in the same patients produce the same estimate of disease load and location, and secondly, to study possible association between the bone disease detected by these scans and the effect on disease outcome and survival. Bone disease occurs in about 90% of multiple myeloma (MM) patients. There are no data comparing the new diagnostic modalities with WB-MRI and MIBI in MM. Design: A prospective comparative study between WB-MRI and MIBI scans in assessing bone disease and outcome of MM. Participants and methods: Sixty-two consecutive patients with confirmed MM underwent simultaneous WB-MRI (both axial T1 and turbo spin echo short tau inversion recovery (STIR)) and MIBI scans at a single institution from January 2010 to January 2011, and their survival status was determined in January 2012. The median age was 62 years (range 37–88) with a male-to-female ratio of 33 : 29. Results: In vertebrae and long bones, MRI scan detected more disease compared with MIBI scan (p<0.001) but there was less difference in the skull (p=0.09). In the ribcage, the MIBI scan detected more lytic lesions of the ribs compared with MRI scan (p<0.001). Thirteen of the 62 patients died during the 24-month follow-up. Increased disease detected in all bones by both scans was associated with increased mortality risk (MIBI p=0.001; MRI-STIR p=0.044; but not MRI-T1 p=0.44). In all combined bone groups, the mean MIBI scan results provided a better prediction of mortality than MRI scan over the follow-up period (MRI-T1 vs MIBI p=0.019; MRI-STIR vs MIBI p=0.047). Conclusions: Although WB-MRI detected more MM bone disease, MIBI scan predicted overall disease outcome and mortality better than MRI scan. Further studies to define optimum use of these imaging techniques are warranted. Trial registration number: The study was registered prospectively in the Australian and New Zealand Clinical Trials Registry at http://www.ANZCTR.org.au under No: ACTRN12609000761268.